THE SOLVE PROBLEMATICS OF FACILITIES AND INFRASTRUCTURE LEARNING LANGUAGES AND LITERATURE INDONESIA THROUGH FIELD OBSERVATION - Anis Heni; Lilis Faridah; Dovila Johansz (JLER (Journal of Language Education Research), 2018)
The problem of infrastructure facilities in learning Indonesian language and literature is very important to be handled, because it is very influential in the smoothness of teaching and learning process, infrastructure facilities as learning facilities must be met in accordance with the needs of scientific development. The problem that often arises later is the uncontrolled plan programmed by the school, as the organizer of the school facilities. This can happen because the school does not know the standard of infrastructure that must be fulfilled. To overcome these problems required adequate Infrastructure and meet the needs of the standard. Because the Facility and Infrastructure of this school is one of supporting the achievement of quality education and to improve the quality of teaching and learning process, then we feel the need to conduct this research. The purpose of this study is to obtain information on the condition of infrastructure facilities in learning Indonesian language and literature in schools with field observation, using survey, literature study, documentation, and interviews. There are several stages of research are: (1) Preliminary study to carry out coordination and data collection on the object under study; (2) Field survey to obtain data on the achievement of educational facilities and infrastructures; (3) to obtain data on the use of infrastructure as supporting learning process; (4) Data processing to know the mapping condition of learning facilities and infrastructure that exist on the object studied; and (5) Formulation of conclusions, and suggestions.